Merging Feedback in Process Approach to Develop Students’ Ability in Writing an Effective Paragraph - Rita Handayani (English Department - Universitas Sultan Ageng Tirtayasa, 2022)
Many studies have been conducted to demonstrate the efficacy of either the process approach or feedback on students' writing achievement. Earlier studies primarily used feedback to improve students' grammatical and writing accuracy. However, studies that focus on providing feedback to improve the content of students' writing are hard to come by. This study aims to bridge that gap. The process approach was used in this study, with feedback focusing on the content and organization of students' writing. Purposive sampling was used to select 35 second-semester students from the English study program at Sultan Ageng Tirtayasa University. Data was gathered through the use of questionnaires, observations, and writing tests. To determine the validity and reliability of the data, a detailed assessment rubric criterion and an assessment of writing results given by two raters were used. The results of this study show that combining process approaches with feedback has a significant impact on improving students' skills in writing effective English paragraphs. The most significant improvements are on the aspect topic development, topic sentence writing, and ideas organization. This suggests that combining a process approach with feedback is beneficial in improving students’ skill in writing effective paragraphs.